The Role of Rotifera as Sentinel Organism of Trophic Structure on Freshwater Ecosystems - Bhandarkar, Sudhir; Bansod, Sonam (International Journal of Scientific Research in Biological Sciences, 2025)
For determining the trophic condition of freshwater ecosystems, rotifera, a phylum of tiny and near-microscopic pseudocoelomate creatures, are important sentinel or bioindicator species. For ecological monitoring and water quality evaluation, they are perfect because of their species composition, variety, and abundance, which react quickly and sensitively to changes in environmental quality and nutrient availability. Aquatic environments consist of both biotic and abiotic interactions. There is a relationship between these things. They create an ecosystem's cumulative environmental condition, which can be classified as oligotrophic, mesotrophic, or eutrophic at present. Of all the diverse types of plants and animals that live in water, zooplankton are crucial for controlling the systematic processes that keep the environment healthy. Rotifers are one of the planktonic groups of zooplanktons that perform very well in controlling the ecosystem as a whole. These large organisms are also occasionally seen as an avoidable instrument for determining the state of the environment. It is always appropriate to use these creatures as bio-indicators of the ecosystem's trophic structure and pollution level. A good bio-indicator of water quality might be the group of rotifers or a single species, depending on the many indexes and the link between various biological, chemical, and physical features such as the dynamics and diversity of the described organism. Rotifers react strongly to eutrophication, or nutrient enrichment, especially when it comes to the availability of phosphate and nitrogen.